The Genetic Variation of Bali Cattle (Bos javanicus) Based on Sex Related Y Chromosome Gene - Winaya, A; Rahayu, ID; Amin, M; Herliantin, Herliantin (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
Bali cattle is very popular Indonesian local beef related to their status in community living process of farmers in Indonesia, especially as providers of meat and exotic animal. Bali cattle were able to adapt the limited environment and becoming local livestock that existed until recently. In our early study by microsatellites showed that Bali cattle have specific allele. In this study we analyzed the variance of partly sex related Y (SRY) gene sequence in Bali cattle bull as a source of cement for Artificial Insemination (AI). Blood from 17 two location of AI center, Singosari, Malang and Baturiti, Bali was collected and then extracted to get the DNA genome. PCR reaction was done to amplify partially of SRY gene segment and followed by sequencing PCR products to get the DNA sequence of SRY gene. The SRY gene sequence was used to determine the genetic variation and phylogenetic relationship. We found that Bali cattle bull from Singosari has relatively closed genetic relationship with Baturiti. It is also supported that in early data some Bali bulls of Singosari were came from Baturiti. It has been known that Baturiti is the one source of Bali cattle bull with promising genetic potential. While, in general that Bali bull where came from two areas were not different on reproductive performances. It is important to understand about the genetic variation of Bali cattle in molecular level related to conservation effort and maintaining the genetic characters of the local cattle. So, it will not become extinct or even decreased the genetic quality of Indonesian indigenous cattle. Key Words : Bali cattle, SRY gene, artificial insemination, phylogenetic, allele Animal Production 13(3):150-155 (2011)